2018
DOI: 10.5271/sjweh.3709
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured physical activity of hospital shift workers

Abstract: Objectives Shift work may alter workers' leisure-time and occupational physical activity (PA) levels, which might be one of the potential underlying mechanisms of the negative health effects of shift work. Therefore, we compared objectively measured PA levels between hospital shift and non-shift workers. Methods Data were used from Klokwerk+, a cohort study examining the health effects of shift work among healthcare workers employed in hospitals. In total, 401 shift workers and 78 non-shift workers were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 45 publications
2
28
1
Order By: Relevance
“…For example, studies have found that night shift workers are not exercising less than the general population. 9 They may even be exercising more than their day-shift counterparts. 9,10 A growing body of research suggests that discordance with the circadian rhythm is an independent risk factor for the development of metabolic syndrome.…”
Section: Demographics Of Shift Workersmentioning
confidence: 99%
“…For example, studies have found that night shift workers are not exercising less than the general population. 9 They may even be exercising more than their day-shift counterparts. 9,10 A growing body of research suggests that discordance with the circadian rhythm is an independent risk factor for the development of metabolic syndrome.…”
Section: Demographics Of Shift Workersmentioning
confidence: 99%
“…Therefore, in cross-sectional studies, the difference observed in the physical activity between day and night workers was likely to have been confounded by participants' personal characteristics. Lately, several studies utilizing objective measurement of physical activity documented no association between shift work and total leisure-time physical activity (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Based on the results of the current study, we found no evidence that physical activity is an underlying mediator linking shift work and ILI/ARI incidence rate. As found earlier, physical activity levels of shift and non-shift workers during leisure were similar, but shift workers were more physically active at work (18). However, an association between physical activity and ILI/ARI incidence rate, and thus the association between mediator and outcome, was lacking.…”
Section: Discussionmentioning
confidence: 59%
“…Potential mediators: sleep, physical activity, and diet. To determine sleep and physical activity levels, participants were instructed to wear triaxial accelerometers (Actigraph GT3X devices, Actigraph, Pensacola, FL, USA) that were taped to their thigh, for 24 hours/day, for seven consecutive days (18). During these days, participants kept a diary in which work, sleep, and non-wear times were reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation